Kepuasan Khalayak Menonton Tayangan On The Spot di Stasiun Televisi Trans 7 - Tuti Widiastuti; Rajab Ritonga; Marsetio Marsetio (Jurnal Pewarta Indonesia, 2023)
This study aims to examine "Factors Affecting the Level of Audience Satisfaction On The Spot Trans 7". From this research, it is expected to know the things that influence the level of audience satisfaction in consuming media, one of which is On The Spot. The main theory used as the basis for this research is the Uses and Gratifications Theory. The research method used is a quantitative research method, namely data collected in the form of numbers which will be tested using the media effects research method and the data is processed using the SPSS program. The end result of this research is that demographic matters do not affect the gratification that the audience is looking for. Meanwhile, factors from the media and the social environment have an effect on audience gratification satisfaction. research scope.